Implementation of Government Policy in Alor Regency, East Nusa Tenggara regarding Guiding Football Sports as Priority Sports (Journal of Physical Education and Sports, 2019)
This study aims to analyze the implementation of the Alor Regency Government Policy, East Nusa Tenggara about Guidance, human resources, facilities and infrastructure, competition, and funding for soccer sports as priority sports. This research method uses a qualitative approach with ethnographic design. The technique of collecting data uses observation, interviews, and documentation. Research subjects of the DPRD, KONI, Dispora, trainers, sports teachers, and athletes. Data analysis techniques: data reduction, data presentation, and drawing conclusions/verification. Research result: Implementation of government policies regarding achievement coaching is regulated in the Regional Regulations and Regent Regulations, Government policies regarding licensed trainer human resources have not been programmed, Government policies regarding facilities and infrastructure have not all been fulfilled, Local government policies regarding the organization of competition have not been maximized, Government policies regarding funding are in accordance with RKA-SKPD and government grants sourced from the APBD. The conclusions of the research on the Policy Implementation of Alor Regency Government, East Nusa Tenggara regarding the Development of Football Sports as Priority Sports have not been following the Regional Regulations and Regent Regulations with funding constraints adjusted to the regional budget.